“And Dahlia as well will be a shadow or a cloud in a little while”: The Auto/biographical Poetics of the Story “Kitzur Toldot Michal” by Dahlia RavikovitchRavikovitch - Ben-Zvi Morad, Yael (MiKAN, 2024)
The story “Kitzur Toldot Michal” (An abridged history of Michal) by Dahlia Ravikovitch is a biography of the author’s mother - Michal. The life stories of both author and her mother are interwoven, with the two portraits mirroring one another. This is a biographical story with two main characters, negating the possibility of drawing a unitary human portrait and a linear life story. It is an autobiographical story hidden behind a biographical tale of the author’s mother.The article focuses on the techniques used in the story, which break down the rules of the biographical and autobiographical genres: the two biographical genres are fused and they are used together with fictional genres, splitting the main character between different identities as well as merging with other characters. The narrative is based on repetition, circularity, and allusion, which interfere with the construction of the customary chronological-developmental sequence of life stories.The article examines how this dissolution of subjective identity and of the narrative nevertheless draw a complex portrait of the author and her life story, despite the deviation from the principles of the genre, or rather because of it. The theoretical framework for the analysis is the work of Paul de Man, who defined autobiography as a type of writing that inevitably hides in other genres, constituting a bridge between life and death, like writing on tombstones. Ravikovitch’s short stories tend to be considered as lower-quality literature compared to her poems. However, this article points out that the stories were written with the same poetic building blocks Ravikovitch used for her poems. Understanding them is necessary to build Ravikovitch’s poetic lexicon as a complex system of intertextual and intratextual allusions. Out of this self-referential poetic space grows the figure of the poet and the story of her life as a kind of riddle whose solution is elusive.